1988
DOI: 10.1161/01.res.63.4.735
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin is a determinant of neutrophil sequestration in the lung.

Abstract: We investigated the role of fibrin in the sequestration of neutrophils hi lungs challenged with microembolism. Lungs of chronically prepared awake sheep were imaged after Infusion of '"In-neutrophils and ul I-fibrinogen. Thrombin (80 units/kg) was administered to induce fibrin sequestration hi the lung. One group received tranexamic add (4 mg/kg i.v.) to inhibit fibrinolysis, and the control group received a saline infusion. Thrombin infusion increased both u 'I-fibrinogen and "'In-neutrophils hi the lung, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…We have demonstrated that tPA possesses antiinflammatory properties in addition to the well-characterized fibrinolytic activity (2,21). Taken together, the antiinflammatory and fibrinolytic activities of tPA could prove beneficial in the treatment of ARDS because the condition is associated with both an acute inflammatory response and fibrin deposition (22)(23)(24). The data presented in this study support the feasibility of formulating tPA for nebulization and pulmonary delivery.…”
Section: Discussionsupporting
confidence: 64%
“…We have demonstrated that tPA possesses antiinflammatory properties in addition to the well-characterized fibrinolytic activity (2,21). Taken together, the antiinflammatory and fibrinolytic activities of tPA could prove beneficial in the treatment of ARDS because the condition is associated with both an acute inflammatory response and fibrin deposition (22)(23)(24). The data presented in this study support the feasibility of formulating tPA for nebulization and pulmonary delivery.…”
Section: Discussionsupporting
confidence: 64%
“…The action of plasmin in inducing neutrophil adherence is comparable in magnitude and time course to other neutrophil adhesion-promoting mediators such as C5a and FLMP, which act primarily on neutrophils (17). These agents also increase neutrophil adhesiveness over a short time (i.e., within 1 h).…”
Section: Discussionmentioning
confidence: 89%
“…The rapidity of the adherence response is compatible with increased functional activity of CD1 8 without translocation of CD1 8 glycoprotein from the cytoplasmic storage granules to the cell surface (39). The persistence of the plasmin effect for up to 30 min after washing is in contrast to effects of other mediators such as C5a (17) and LTB4 (20), which result in a rapid modulation of neutrophil adherence.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations